A Customized Input Device for Simulating the Detection of Hazardous Materials - Gainer, Scott; Eadara, Suraj; Haskins, Jason; Huse, Will; Zhu, Bolin; Boyd, Blake; Laird, Charles; Farantatos, JJ; Jerald, Jason (2020 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2020)
Although consumer VR controllers work well for gaming and general VR usage, they are not necessarily appropriate for specific professional needs. Instead of attempting to build generalized hand controllers with the goal of satisfying a broad range of users, we built a novel input device for the specific needs of a specific target audience--firefighters. We accomplished this by talking with over 30 firefighters. Their input was in the form of one-on-one discussions, focus groups, questionnaires, and feedback on our work in progress. Based on their input, we 1) identified a specific need-- the simulation of detecting hazardous materials, 2) built a physical air monitoring device, that more closely matches firefighters actual air monitoring devices than standard VR controllers, and 3) implemented a hazardous materials scenario that consist of both physical and virtual elements.